Clinicodemographic Profile and Clinical Outcome of Children Presenting to Telemedicine Center at Institute of National Importance of India: A Prospective Observational Study - N. Yankappa; Anil Kumar; Arun Prasad; Lokesh Tiwari; Pradeep Kumar (International Journal of Telemedicine and Applications)
Background. There is a global shortage of healthcare professionals, especially in developing countries, leading to disparities in access to healthcare, worsened by the pandemic. Telemedicine is emerging as a solution, with growing adoption worldwide due to advancements in technology and increased awareness. Research Problem. The establishment of telemedicine depends on resources, infrastructure, and knowledge about healthcare needs. Further studies are needed to monitor and address evolving issues in telemedicine. The Overall Purpose of the Study. Rural health disparities stem from multiple factors, like limited healthcare access, workforce shortages, lifestyle choices, and lower socioeconomic status, leading to higher mortality and chronic diseases. Addressing these challenges is vital for rural community well-being. Telemedicine centers present a promising solution, bridging gaps, and improving healthcare outcomes for underserved remote populations. Methodology. Objective: This study assessed the clinicodemographic profile and clinical outcome of children presenting to the telemedicine center at the Institute of National Importance in India. Design: Prospective observational study. Setting: A single-center tertiary care level. Participants: This study included 79 children aged up to 18 years. Major Findings and Summary of Interpretations. In our study, 79 children using telemedicine found a near-equal gender distribution. 8.9% needed emergency care, with common complaints being respiratory issues, fever, abdominal pain, and vomiting. After two weeks, 83.5% showed improvement, emphasizing telemedicine’s effectiveness in pediatric care. Conclusion. Our study underscores telemedicine’s positive impact on pediatric healthcare, emphasizing its potential to enhance access, outcomes, and cost-efficiency. Wider telemedicine adoption can reduce morbidity and mortality, support preventive care, and streamline posttreatment services, alleviating pressure on specialized facilities. While our focus was pediatrics, the telemedicine model is adaptable to various age groups and conditions, but it should be seen as a valuable supplement to, not a total substitute for, in-person healthcare visits.